Dari Soft Selling ke Pemaknaan Khalayak: Analisis Resepsi Generasi Z terhadap Kolaborasi Jiniso x Aqeela Calista di TikTok - Angel Nurhidayat; Rocky Prasetyo Jati (Yayasan Literasi Sains Indonesia, 2026)
This study examines Generation Z audience perceptions of collaborative content between local fashion brand Jiniso and artist Aqeela Calista on the TikTok account @jiniso.entertainment. Brand-influencer collaboration on TikTok has become a dominant marketing strategy; however, understanding of how audiences actively construct meaning toward such content remains limited in the Indonesian digital marketing communication context. This study employs Stuart Hall's reception analysis as the primary analytical framework, with data gathered through netnography and in-depth interviews with five informants. Audience meaning-making was mapped across three decoding positions: dominant-hegemonic, negotiated, and oppositional. Findings reveal that the majority of audiences occupy the dominant-hegemonic decoding position (three of five informants), followed by the negotiated position (two informants), with no oppositional position identified. Message acceptance is shaped by three primary factors: (1) Aqeela's credibility as an endorser perceived as natural and relevant to the Gen Z target audience; (2) successful cultural meaning transfer from Aqeela to the Jiniso brand; and (3) a soft-selling strategy packaged as entertainment content. The content's impact generally halts at the awareness and interest stages, falling short of purchase conversion.